TINDAK PIDANA KEJAHATAN VIRTUAL DALAM GAME ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Muhammad Iqbal Dzulfikar; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Virtual Crime in Online Games is a new thing in society and is also animportant problem for people in the country. The form of the regulation regardingvirtual crime in Online Games is Law Number 19 of 2016 concerningamendments to Law Number 11 of 2008 concerning Information and ElectronicTransactions, in this Law it is regulated regarding the absence of virtual crimes.The purpose of writing this thesis: First, I want to know how the modus operandior how virtual crime according to Law Number 19 of 2016 concerningamendments to Law Number 11 of 2008 concerning Information and ElectronicTransactions. Second, I want to know about the criminalization of virtual crimesin online games in Law Number 19 of 2016 concerning Amendments to LawNumber 11 of 2008 concerning Information and Electronic Transactions.The type of research used in this research is normative legal research. Theapproach used by the researcher is normative juridical approach. Analysis of thedata used is the author analyzes the data qualitatively by justification. In drawingconclusions, the author uses deductive thinking method, namely a way of thinkingthat draws conclusions from a general statement or proposition into a specificstatement.From the results of the study, one of the works of criminal act at virtualcrimes in online games is virtual object transactions, but the perpetrators arguethat the virtual goods will be given soon, until when they ask again about thevirtual goods, the perpetrator then blocks the victim's number so that the victimfeels aggrieved. However, in this case, Law Number 19 of 2016 concerningamendments to Law Number 11 of 2008 concerning Electronic Information andTransactions in article 32. Furthermore, the punishment for perpetrators ofvirtual crimes, namely cyberstalking and the difference between it andcyberbullying according to the law, if several elements are fulfilled in LawNumber 19 of 2016 concerning amendments to Law Number 11 of 2008concerning Information and Electronic TransactionsKeywords: Criminal act – Virtual Crime – Law on Information and ElectronicTransactions